Long-term outcome of lower extremity bypass surgery in diabetic and non-diabetic patients with critical limb-threatening ischaemia in Germany - Surmann, Johanna; Meyer, Philipp; Epple, Jasmin; Schmitz-Rixen, Thomas; Böckler, Dittmar; Grundmann, Reinhart T. (Biomedicines, 2024)
Aim: To present the short- and long-term outcomes of lower extremity bypass (LEB) surgery in patients with critical limb-threatening ischaemia (CLTI), comparing diabetic (DM) and non-diabetic (non-DM) patients. Methods: Retrospective analysis of anonymised data from a nationwide health insurance company (AOK). Data from 22,633 patients (DM: n = 7266; non-DM: n = 15,367; men: n = 14,523; women: n = 8110; mean patient age: 72.5 years), who underwent LEB from 2010 to 2015, were analysed. The cut-off date for follow-up was December 31, 2018 (mean follow-up period: 55 months). Results: Perioperative mortality was 10.0% for DM and 8.2% for non-DM (p < 0.001). Patients with crural/pedal bypasses (n = 8558) had a significantly higher perioperative mortality (10.3%) than those with above-the-knee (n = 7246; 5.8%; p < 0.001) and below-the-knee bypasses (n = 6829; 8.9%; p = 0.003). The 9-year survival rates in DM patients were significantly worse, at 21.5%, compared to non-DM, at 31.1% (p < 0.001). This applied to both PAD stage III (DM: 34.4%; non-DM: 45.7%; p < 0.001) and PAD stage IV (DM: 18.5%; non-DM: 25.0%; p < 0.001). Patients with crural/pedal bypasses had a significantly inferior survival rate (25.5%) compared to those with below-the-knee (27.7%; p < 0.001) and above-the-knee bypasses (31.7%; p < 0.001). Conclusion: Perioperative and long-term outcomes regarding survival and major amputation rate for CLTI patients undergoing LEB are consistently worse for DM patients compared to non-DM patients.
Gesehen am 04.11.2024
Erstveröffentlichtung online: 22. Dezember 2023